Image schematic analysis of Bangla postpositions - Bagchi, Tanima; Kumar, Rajesh (Acta Scientiarum. Language and Culture, 2018)
Spatial relationships are fundamental in shaping our interactions with the physical world. They also play a significant role in our construal of abstract ideas in terms of space. In order to understand this transfer of ideas from concrete to abstract space, image schematic approach is applied to analyze role of adpositions in a number of languages. This paper attempts to analyze conceptualization of postpositions in Bangla using image schematic approach. In Bangla, nominal postpositions are derived by suffixing locative suffix -/e/ with the noun. However, this suffix is also used as an independent postpositional marker in Bangla. Therefore, this paper attempts to understand image schema of this locative suffix in different contexts. The basic image schema of this locative suffix is observed to be that of container schema. However, functional component of this containment relation varies across different contexts. Further, two spatial postpositions of Bangla are analyzed indicating that locative suffix -/e/ primarily carries the sense of space in these two nominal postpositions of space. This analysis helps to understand how meanings of these nouns interact with meaning of locative suffix to form nominal postpositions using image-schema. These differences in meanings have resulted in their different distributional and usage patterns.